High-frequency monitoring through in-situ fluorometric sensors: A supporting tool to long-term ecological research on lakes - Rogora, Michela; Cancellario, Tommaso; Caroni, Rossana; Kamburska, Lyudmila; Manca, Dario; Musazzi, Simona; Tiberti, Rocco; Lami, Andrea (Frontiers in Environmental Science, 2023)
Lake Maggiore is a site of the Long-Term Ecosystem Research (LTER) network, belonging to the deep subalpine Lake District in Northern Italy. Studies on physical, chemical, and biological features of the lake have been performed continuously since the 1980s. The lake recovered from eutrophication reaching the present oligotrophic condition. In the last decade, climate change represents the main driving factor for the long-term evolution of the lake, affecting its hydrodynamics, nutrient status and biological communities. In 2020 a high frequency monitoring (HFM) system was deployed, with the aim to integrate the long-term monitoring based on discrete sampling and analysis. The system consists of a buoy equipped with sensors for limnological variables and algal pigments. The HFM program is part of a cross-border project between Italy and Switzerland focusing on lake quality monitoring as a critical input for successful lake management. In this paper we focus on Chlorophyll-a data, with the aim to test whether in-situ fluorescence measurements may provide a reliable estimate of lake phytoplankton biovolume and its seasonal dynamic. Sensor’s performance was regularly tested comparing chlorophyll-a data taken by the in-situ fluorescent sensors (Cyclops7, Turner Design), data from laboratory fluorescence analysis (FluoroProbe, BBE Moldaenke), values obtained from chlorophyll-a analysis by UV-VIS spectrophotometry and data from phytoplankton microscopy analysis. We found a general good agreement between the Chlorophyll-a data obtained with the different methods, confirming the use of in-situ sensors as a reliable approach to measure algal pigments, especially to assess their variability in the short-term, but also to describe the seasonal pattern of phytoplankton biovolume. However, phytoplankton community composition played a substantial role in the performance of the different methods and in the reliability of in-situ data as a tool to assess algal biovolume. This study demonstrates that HFM, used in conjunction with discrete chemical and biological monitoring, represents an important advance and support in the long-term monitoring of freshwaters and a useful tool to detect ecological changes. Regular check and validation of the sensor readings through laboratory analyses are important to get trustworthy data.